Quality of life after total laryngectomy: functioning, psychological well‐being and self‐efficacy. Issue 4 (19th February 2015) - Perry, Alison; Casey, Erica; Cotton, Sue
Abstract Background Quality of life (QoL) is an important construct when assessing treatment outcomes. Aims To examine the relative contributions of functioning, psychological well‐being and self‐efficacy on self‐perceived QoL with a sample of total laryngectomy patients in Australia who had surgery for advanced laryngeal cancer. Methods & Procedures In a cross‐sectional study, 113 members of the Laryngectomy Associations of New South Wales and of Victoria, Australia, were recruited, and each was sent a series of questionnaires for postal return. Four psychometrically validated measures were used for participants to document their QoL, functioning (speech, swallowing), psychological well‐being and general self‐efficacy. Outcomes & Results Eighty‐six (77%) questionnaires were returned and 83 were analysed. The cohort consists of 70 men and 13 women aged between 46 and 88 years. Overall, this sample of total laryngectomy survivors demonstrated significantly reduced physical health QoL (p < 0.001) and social relationship QoL (p = 0.011) and higher levels of depression (p = 0.008) and anxiety (p = 0.001) when compared with normative samples. This was in the context of them having higher than normal self‐efficacy scores and, at worst, mild (self‐rated) impairment of speech and of swallowing. Psychological well‐being (sr2 = 0.43, p < 0.001) had a stronger association than functioning (speech, swallowing, sr2 = 0.08, p < 0.05) for their psychological QoL. Psychological well‐being (sr2 = 0.17, p < 0.001) and not functioning (sr2 = 0.05, p > 0.05) were significantly associated with social relationship QoL. Self‐efficacy scores were significantly higher than norms in this cohort, but were not associated with either their psychological QoL or social relationship QoL, after controlling for psychological well‐being and functioning. Conclusions & Implications For survivors of laryngeal cancer treated by total laryngectomy, it is important to be aware of the impact of psychological well‐being (depression, anxiety, stress) on self‐perceived QoL. In addition to rehabilitating function (speech, swallowing), specific interventions to assist these individuals better manage their psychological well‐being will likely improve their perceived life satisfaction/QoL.